Governance of the Business Ecosystems to Commercialize Beekeeping Activities in Emerging Markets - Tutuba, Nicholaus Bhikolimana; Tundui, Hawa Petro; Msamula, Jasinta Samwel (Journal of Strategic Innovation and Sustainability, 2020)
Business ecosystems do not occur naturally, it needs an orchestrator to align and govern actors to co-create value and appropriate value. This qualitative action research analyzed the structure and governance of the beekeeping industry in Tanzania. The transaction-based market relations should be changed to a collaborative model by aligning value chain actors in the beekeeping industry through the honey collection centre. Also, the value should be appropriated and shared among participating firms in a fairly and truthful way. The orchestrator should make sure that beekeepers join and stay in the ecosystem. Policymakers, researchers, and organization should adopt the ecosystem-as-structure approach to build and govern a commercial beekeeping ecosystem.